Potencialidades de veículos microemulsionados para fotoprotetores físicos - Surman, Luciana L.; Barbosa, Leonardo M.Q.; Siqueira, Scheyla D.V.S.; Silva, Kattya G.H.; Oliveira, Anselmo G. [UNESP]; Egito, E. Socrates T. (My University, 2009)
The human solar exposition at UVA and UVB radiation is a subject strongly studied in the pharmaceutical and dermocosmetical field. The dermal protection became, therefore, a main subject of study because of its importance on the health of cutaneous tissue. This review deals with such problem. First, the theoretical aspects related with solar irradiation will be discussed. Then, the technological approach about the development of sunscreen products is mentioned. Finally, the viability of microemulsified systems as carriers for sunscreen agents is studied. After a discussion about the theoretical potentialities of such systems, its applicability as nano-carriers for dermocosmetic products is briefly pointed out. Concluding, an approach about the perspectives of such new products is made, revealing their potentialities in the market of sunscreen products.
Potentiality of microemulsions as a carrier for sunblock products
Keywords: Dermocosmetics; Microemulsions; Nanotechnology; Sunscreen roducts